MATERI BIOLOGI MENGGUNAKAN PEMBELAJARAN CTL (Contextual Teaching and Learning) PADA SISWA DI KELAS VIII-F SMP NEGERI 9 PURWOKERTO - Mulyadi Mulyadi; Teguh Julianto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This research is a Classroom Action Research that aims to improve students' learninginterest in science learning biology materials. Indicators of student interest aspectsobserved include diligent follow the learning process, active tasks, attention to followthe learning process and completeness of tools or learning resources. The resultsshowed an increase in the interest aspect. The percentage of increased interest inlearning in the first cycle of 39.5%, on the second cycle of 72.67% and in the thirdcycle of 80.92%. Increased interest in student learning has a positive impact onimproving learning outcomes. Percentage of learning success or class completeness inthe first cycle of 39%, on the second cycle of 82%, and in the third cycle of 93%. Theresult of this research can be concluded that learning CTL (Contextual Teaching andLearning) can improve students' learning interest in science learning biology materialin VIII F SMP Negeri Purwokerto.Keywords: improvement, interest in learning, contextual learning, mastery learning